PERSPECTIVES OF UKRAINIAN RAILWAY TOURISM DEVELOPMENT ON NARROW-GAUGE LINES OF ZAKARPATTIA - Kuznetsov, V. G.; Pshinko, P. O.; Klimenko, I. V.; Gumenyuk, A. V.; Zahorulko, S. M. (Science and Transport Progress, 2015)
Purpose.The purpose of the paper is: (1) the definition of perspectives development of Ukrainian railway tourism on the narrow gauge lines of Zakarpattia; 2) technical condition analysis of Borzhava narrow gauge railway for the project to restore the effective functioning of mountain railways track, width 750 mm in the Carpathian region, with the possibility of their accession to the distributed travel network; 3) the study of the modern state and tendencies of development of tourist industry of Ukraine and the passenger economy of national railways; 4) clarification of the role and place of the railway tourism in the transportation system. Methodology. The expert group has carried out field inspections and field investigations of facilities track facilities and passenger infrastructure, rolling stock and ancillary industries involved in the functioning narrow-gauge railway. It was estimated the overall technical condition of the railway track and engineering structures section of narrow-gauge Railways in the Carpathian region. Findings. In the framework of on-site examinations of the expert group found that the objects of tracks, passenger and freight infrastructure, rolling stock and ancillary industries involved in the operation of narrow-gauge Railways are in poor condition and require significant updates and major repairs. But the routes of passenger trains remain fit for participation in the project of development of railway tourism of Ukraine Originality. For the first time the state of the narrow-gauge railway for further implementation of the project on the development of rail tourism in Ukraine was realized. The analysis of foreign experience of organization of railway tourism has been carried out. The modern state and tendencies of development of tourist industry of Ukraine was studied, the factors of competitiveness of rail transport for providing tourist transport in Ukraine were identified and systematized.Practical value. The recovery and effective functioning of mountain railways with a width of 750 mm in the Carpathian region will give an impetus to the tourism development, engineering, construction and energy. At the same time, these actions will allow us to finally implement a scientifically-based effective flood control measures that will protect the population from natural environmental disasters.